Magmatisme et conditions de construction de textes de savoirs problématisés au collège - Hanaà Chalak (Recherches en Éducation)
Severa studies consider that the school knowledge, as it taught to the pupils, is limited to propositional texts revealing the true results of science without any correlation to the problems. To study the conditions of construction of prblematized kwoledge texts, we set up, within a research team, a “forced” sequence in grade 8 concerning the proble of the origin of the volcanic activity. We analyze the knowledge texts produced by the class during the sequence to know if they carry the tracks of the problematized or if they expose only the solutions. This analysis will allow us to make a praxeologic modeling of the teaching practices and to study techniques mobilized in the forced sequence. It appears that problematized texts requires of teaching actions leading to leaps of abstraction, allowing a work of abstraction and generalization of the problem posed.